Resolutions Against Uniqueness. - Lota, Kenji; Hlobil, Ulf (Erkenntnis, 2023)
The paper presents a new argument for epistemic permissivism. The version of permissivism that we defend is a moderate version that applies only to explicit doxastic attitudes. Drawing on Yalcin's framework for modeling such attitudes, we argue that two fully rational subjects who share all their evidence, prior beliefs, and epistemic standards may still differ in the explicit doxastic attitudes that they adopt. This can happen because two such subjects may be sensitive to different questions. Thus, differing intellectual interests can yield failures of uniqueness. This is not a merely pragmatic phenomenon.